Best practices for monitoring, mitigation, and preservation of cultural heritage sites affected by geo-hazards: the results of the PROTHEGO project - Themistocleous, Kyriacos; Danezis, Chris; Frattini, Paolo; Crosta, Giovanni Battista; Valagussa, Andrea (My University, 2018)
PROTHEGO (PROTection of European Cultural HEritage from GeO-hazards) utilized novel space technology to monitor surface deformation with mm precision to analyze the impact of geo-hazards in cultural heritage sites in Europe. The project, which took place over 30 months, included the 395 monuments of UNESCO in Europe to monitor geo-hazards, with case studies conducted in 4 UNESCO sites in England, Spain, Italy and Cyprus. The PROTHEGO project used long-term low-impact monitoring systems, such as UAVs and geodetic techniques, as well as InSAR data to monitor and assess the risk from natural hazards on the archaeological site to evaluate potential geo-hazards. This paper will present an overview of best practices for the innovative diagnosis, monitoring, mitigation and preservation of Cultural Heritage monuments sites affected by geo-hazards that are potentially unstable due to landslides, sinkholes, settlement, subsidence, active tectonics as well as structural deformation, which are based on the results of the 4 case studies featured in the project. The PROTection of European Cultural HEritage from GeO-hazards (PROTHEGO)" project HERITAGE PLUS/0314/36 is funded in the framework of the Joint Programming Initiative on Cultural Heritage and Global Change (JPICH)-HERITAGE PLUS under ERAâNET Plus and the Seventh Framework Programme (FP7) of the European Commission and the Cyprus Research Promotion Foundation, contract KOINA/Î ÎšÎ-HERITAGE PLUS/0314/36.
Keywords: Cultural Heritage; Geodetic techniques; JPI; Natural hazards; PROTHEGO; Remote sensing; UAV